Quinine pharmacokinetics in cerebral malaria: predicted plasma concentrations after rapid intravenous loading using a two-compartment model. - Davis, T; White, N; Looareesuwan, S; Silamut, K; Warrell, D (1988)
To investigate the toxic potential of rapid intravenous quinine administration in severe malaria, the pharmacokinetic properties of low-dose quinine dihydrochloride injection (4 mg/kg body weight, equivalent to 3.3 mg base/kg) followed one hour later by infusion of 16 mg/kg over 3 h were studied in 7 patients with cerebral malaria. Plasma quinine concentrations closely followed a bi-exponential decline. Both the volumes of the central compartment (mean +/- SD: 0.17 +/- 0.10 litre/kg) and total volumes of distribution (0.74 +/- 0.30 litre/kg) were significantly smaller than those previously reported for healthy subjects. Based on the derived pharmacokinetic parameters, predicted plasma quinine concentrations following intravenous injection of the standard therapeutic dose (10 mg salt/kg) over 10-20 min are potentially toxic in severe malaria. Further reductions in administration time would produce disproportionately higher plasma quinine concentrations, especially as the distribution half-time (2.3 +/- 3.2 min) is approached. A theoretical regimen designed to achieve therapeutic, non-toxic plasma quinine concentrations promptly would be 7.0 mg quinine dihydrochloride/kg over 30 min. A subsequent maintenance infusion of 10 mg/kg over 4 h would allow for drug elimination and acute changes in pharmacokinetic parameters due to resuscitation and rehydration.